C-shaped Canal System in the Mandibular Second Molars in a Saudi Arabian Subpopulation Analyzed Using Cone-Beam Computed Tomography - Youssef A. Algarni; Nuha Alghamdi; Ahmed A. Almuashi; Mosa A. Alghobaishi; Abdullah S. Alqahtani; Shashit Shetty Bavabeedu; Wafa Hassan Alaajam (Journal of Pharmacy and Bioallied Sciences)
Background: The superimposition in radiographic images makes it difficult to diagnose C-shaped canals using two-dimensional imaging techniques. A non-invasive technique called cone-beam computed tomography (CBCT) makes it easier to comprehend the C-shaped canal architecture along the root. Aim: This study was undertaken to evaluate C-shaped canals in permanent second molars of mandible in a Saudi Arabian subpopulation using CBCT. Methods: This research was a non-interventional, retrospective clinical trial. CBCT images of 452 mandibular second molars were selected from 300 patients. Every CBCT scan was interpreted by a certified oral radiologist to gather information regarding root canal anatomy, configuration, location, etc. Results: The C-shaped canal was present in 51 (11.28%) of the 452 teeth. The C2 configuration was found to be the most common (28 teeth, 6.19%) followed by C3 (15 teeth, 3.31%), and C1 (7 teeth, 1.54%). Only one tooth (0.22%) had the C5 configuration, and none had the C4 configuration. The C-shaped canal was present in 35 (13.46%) of the 260 teeth from female patients and in 16 (8.33%) of the 192 teeth in male patients (P > 0.05). Conclusion: The overall prevalence of C-shaped canals in mandibular second molars was 11.28% in Saudi population. This arrangement was more common in women than in men.